Apelin as a Candidate for Hypertension Management; a Systematic Review and Meta-Analysis on Animal Studies - Mohammadi, Mohammad; Mohamadi, Mobin; Moradi, Amirreza; Ramawad, Hamzah Adel; Gharin, Pantea; Azizi, Yaser; Yousefifard, Mahmoud (Archives of Academic Emergency Medicine, 2022)
Introduction: Hypertension is a medical emergency that requires immediate medical attention. Recent studies have suggested that peripheral injection of Apelin may lower blood pressure. However, there is no comprehensive conclusion on the role of Apelin in treatment of hypertension. The aim of this systematic review was to evaluate the effects of Apelin on blood pressure in animal studies. Method: Extensive search and data gathering were conducted using keywords related to blood pressure and Apelin on Medline, Embase, Scopus, and Web of Science databases at the end of July 2022. Two researchers screened and summarized the articles independently. Analysis was then conducted based on Apelin dose, route of administration, and follow-up. The findings were reported as standardized mean difference (SMD) with a 95% confidence interval (95% CI). Results: Data from 10 animal studies were included in the present systematic review. Time interval between Apelin administration and blood pressure assessment was 1 to 21 minutes. Findings showed that administration of Apelin immediately reduces mean arterial pressure (MAP) (SMD=-3.13; 95% CI: -4.43 to -1.82; p<0.001), systolic blood pressure (SBP) (SMD= -1.62; 95% CI: -2.22 to -1.02; p<0.001), and diastolic blood pressure (DBP) (SMD= -1.10; 95% CI: -1.59 to -0.62; p<0.001). On follow-up, the effects of Apelin on MAP (meta-regression coefficient=-2.46; p=0.002) and DBP (meta-regression coefficient= -0.16; p=0.012) decreased over time, while the blood pressure lowering effects of Apelin on SBP did not change during follow-up (meta-regression coefficient=-0.17; p=0.063). It was also found that by increasing the dose of Apelin, DBP and SBP further reduced. These findings suggest that the effect of Apelin on SBP (meta-regression coefficient=0.08; p=0.001) and DBP (meta-regression coefficient=0.059; p=0.007) is dose-dependent, and their correlation is significant. Conclusion: The present systematic review showed that peripheral administration of Apelin immediately reduces MAP, SBP and DBP in hypertensive animals. In contrast, central administration of Apelin increases these parameters.